Formation of stable strontium-rich amorphous calcium phosphate: Possible effects on bone mineral. (1st July 2019) - Bussola Tovani, Camila; Gloter, Alexandre; Azaïs, Thierry; Selmane, Mohamed; Ramos, Ana P.; Nassif, Nadine
Graphical abstract: Abstract: Bone, tooth enamel, and dentin accumulate Sr 2+, a natural trace element in the human body. Sr 2+ comes from dietary and environmental sources and is thought to play a key role in osteoporosis treatments. However, the underlying impacts of Sr 2+ on bone mineralization remain unclear and the use of synthetic apatites (which are structurally different from bone mineral) and non-physiological conditions have led to contradictory results. Here, we report on the formation of a new Sr 2+ -rich and stable amorphous calcium phosphate phase, Sr(ACP). Relying on a bioinspired pathway, a series of Sr 2+ substituted hydroxyapatite (HA) that combines the major bone mineral features is depicted as model to investigate how this phase forms and Sr 2+ affects bone. In addition, by means of a comprehensive investigation the biomineralization pathway of Sr 2+ bearing HA is described showing that not more than 10 at% of Sr 2+, i.e . a physiological limit incorporated in bone, can be incorporated into HA without phase segregation. A combination of 31 P and 1 H solid state NMR, energy electron loss spectromicroscopy, transmission electron microscopy, electron diffraction, and Raman spectroscopy shows that Sr 2+ introduces disorder in the HA culminating with the unexpected Sr(ACP), which co-exists with the HA under physiological conditions. These results suggest that heterogeneous Sr 2+ distribution in bone is associated with regions of low structural organization. Going further, such observations give clues from the physicochemical standpoint to understand the defects in bone formation induced by high Sr 2+ doses. Statement of Significance: Understanding the role played by Sr 2+ has a relevant impact in physiological biomineralization and provides insights for its use as osteoporosis treatments. Previous studies inspired by the bone remodelling pathway led to the formation of biomimetic HA in terms of composition, structures and properties in water. Herein, by investigating different atomic percentage of Sr 2+ related to Ca 2+ in the synthesis, we demonstrate that 10% of Sr 2+ is the critical loads into the biomimetic HA phase; similarly to bone. Unexpectedly, using higher amount leads to the formation of a stable Sr 2+ -rich amorphous calcium phosphate phase that may high-dose related pathologies. Our results provide further understanding of the different ways Sr 2+ impacts bone.